Nuclear factor kappa-B- and activator protein-1-mediated immunostimulatory activity of compound K in monocytes and macrophages - Yang, Woo Seok (J Ginseng Res, 2017)
BACKGROUND: Compound K (CK) is a bioactive derivative of ginsenoside Rb1 in Panax ginseng (Korean ginseng). Its biological and pharmacological activities have been studied in various disease conditions, although its immunomodulatory role in innate immunity mediated by monocytes/macrophages has been poorly understood. In this study, we aimed to elucidate the regulatory role of CK on cellular events mediated by monocytes and macrophages in innate immune responses. METHODS: The immunomodulatory role of CK was explored by various immunoassays including cell-cell adhesion, fibronectin adhesion, cell migration, phagocytic uptake, costimulatory molecules, reactive oxygen species production, luciferase activity, and by the measurement of mRNA levels of proinflammatory genes. RESULTS: Compound K induced cell cluster formation through cell-cell adhesion, cell migration, and phagocytic activity, but it suppressed cell-tissue interactions in U937 and RAW264.7 cells. Compound K also upregulated the surface expression of the cell adhesion molecule cluster of differentiation (CD) 43 (CD43) and costimulatory molecules CD69, CD80, and CD86, but it downregulated the expression of monocyte differentiation marker CD82 in RAW264.7 cells. Moreover, CK induced the release of reactive oxygen species and induced messenger RNA expression of proinflammatory genes, inducible nitric oxide synthase, and tumor necrosis factor-alpha by enhancing the nuclear translocation and transcriptional activities of nuclear factor kappa-B and activator protein-1. CONCLUSION: Our results suggest that CK has an immunomodulatory role in innate immune responses through regulating various cellular events mediated by monocytes and macrophages.